Seroprevalence of Chikungunya Fever at a Tertiary Care Hospital (GAIMS Journal of Medical Sciences, 2024)
BackgroundThe Chikungunya (CHIK) is a viral infection caused by CHIK virus which is an arbovirus that belongs to the genus alphavirus under the Togaviridae family. CHIK infection is transmitted to humans by the bite of mosquitoes namely Aedes albopictus and Aedes aegypti. Since Chikungunya fever leads to long term residual arthropathy – like complications which causes hampering in routine work of person after recovery, it is still believed that chikungunya fever is a major burden on public health even in post COVID-19 era.Aims and ObjectivesWe need to understand and evaluate the seroprevalence of chikungunya with reference to its study period, seasonal tendency, need for hospitalization and age-sex distribution.Materials and MethodsA retrospective study was done in 305 suspected samples of chikungunya infection with history of Fever along with joint pain, myalgia between January 2020 to December 2023. Separated serum samples suspected to have Chikungunya infection were subjected to IgM capture ELISA for detection of IgM anti-chikungunya antibodies using IgM antibody capture ELISA produced by National Institute of Virology, Pune, India (NIV, Pune, India). Various statistical tests were done to find out statistical significance with p-value < 0.05 kept as statistically significant.ResultsTotal 305 samples were tested for Chikungunya IgM antibody detection. 55 out of 305 samples were tested positive for CHIK-IgM antibody (18.03%). Out of total 55 positive samples, 32 (58.18%) were belonged to Males and remaining 23 (41.81%) to females (p-value for gender distribution=0.224). The cases varied significantly by age group (p=0.0328), with the highest number of positives from 41-60 years age-group (38.18%). All positive cases having fever and joint pain as chief complaints (p